Autophagic response to cellular exposure to titanium dioxide nanoparticles. (1st October 2018) - Popp, Lauren; Tran, Vinh; Patel, Risha; Segatori, Laura
Graphical abstract: Abstract: Titanium dioxide is "generally regarded as safe" and titanium dioxide nanoparticles (TiO2 NPs) are used in a wide variety of consumer products. Cellular exposure to TiO2 NPs results in complex effects on cell physiology including induction of oxidative stress and impairment of lysosomal function, raising concerns about the impact of TiO2 NPs on biological systems. We investigated the effects of TiO2 NPs (15, 50, and 100 nm in diameter) on the lysosome-autophagy system, the main cellular catabolic pathway that mediates degradation of nanomaterials. Specifically, we monitored a comprehensive set of markers of the lysosome-autophagy system upon cell exposure to TiO2 NPs, ranging from transcriptional activation of genes required for the formation of autophagic vesicles to clearance of autophagic substrates. This study reveals that uptake of TiO2 NPs induces a response of the lysosome-autophagy system mediated by the transcription factor EB and consequent upregulation of the autophagic flux. Prolonged exposure to TiO2 NPs, however, was found to induce lysosomal dysfunction and membrane permeabilization, leading to a blockage in autophagic flux. Results from this study will inform the design of TiO2 NP based devices with specific autophagy-modulating properties.